Rapid pump-controlled replenishment pressure-stabilizing method of the hydraulic support fluid supply system - Chao CAO; Jiyun ZHAO; Kai GAO; Hao WANG; Ran LI; Hao LIU; He ZHANG (Meitan kexue jishu)
A new configuration of a rapid pump-controlled replenishment pressure-stabilizing supply system based on servo pumps is proposed to address the problems of untimely and unreasonable system supply flowrate adaptation during the current hydraulic support follow-up action process, resulting in large system pressure shocks and frequent fluctuations. A calculation model for stable pressure supply flowrate adapted to support action is derived, and a parameter configuration method for servo pump in the rapid pump-controlled replenishment pressure-stabilizing supply system configuration is provided. A co-simulation model of AMESim and Simulink is built, and according to the different pressure stabilized liquid supply flow strategies corresponding to different support actions, the system pressure variation characteristics and support operation period under the multi-pump linkage traditional liquid supply mode and the rapid pump-controlled liquid replenishment pressure-stabilizing liquid supply mode are compared, and experimental verification is conducted. The results show that: according to the pressure change trend of the system and the structure parameters of the actuator, the liquid demand of different actions of the actuator can be accurately obtained, and then the calculation method of the replenishment flow of the pressure regulator can be formed. Combined with the rapid pump-controlled liquid replenishing and stable pressure supply mode, the system pressure fluctuation characteristics were improved and the operation period of the support was accelerated. During the operation of the support, the pressure fluctuation amplitude of the lifting column action and the sequential pushing action were reduced by 23% and 56%, the operation time were shortened by 1.5% and 5%, the system pressure fluctuation times of the descending col-umn and the pulling frame were reduced by 5.7% and 3.2% respectively. During the whole operation of the support, the pressure of the liquid supply system is not lower than the recovery pressure of the unloading valve, the number of system pressure fluctuations is reduced by 25%, and the overall operation time of the support is shortened by 4.2%.